2011
DOI: 10.1007/s00405-011-1579-x
|View full text |Cite
|
Sign up to set email alerts
|

Otorhinolaryngological findings and hearing in HIV-positive and HIV-negative children in a developing country

Abstract: The otorhinolaryngological (ORL) manifestations of Human Immunodeficiency virus (HIV) are common, but remain poorly characterized among children of Sub-Saharan Africa, where 90% of new pediatric infections occur. Our objective was to compare ORL findings and hearing in HIV-positive and -negative children of Luanda, Angola, using a comparative study of 78 outpatients from the HIV polyclinic and of 78 age- and sex-matched controls in a pediatric hospital with interview, general and ORL examination, brainstem aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 16 publications
4
58
1
6
Order By: Relevance
“…Although 6.4% HIV-exposed newborns had mild hearing loss as compared to 2.5% in the non-exposed group, this difference was not significant, however, the mild sensorineural hearing loss has been reported to interfere with language, education and psychosocial development of a child later in life [24, 33]. Sensorineural hearing loss distorts auditory signals as it leaves the cochlea to be processed at higher auditory center thereby incapacitating the development of communication ability of the affected individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 6.4% HIV-exposed newborns had mild hearing loss as compared to 2.5% in the non-exposed group, this difference was not significant, however, the mild sensorineural hearing loss has been reported to interfere with language, education and psychosocial development of a child later in life [24, 33]. Sensorineural hearing loss distorts auditory signals as it leaves the cochlea to be processed at higher auditory center thereby incapacitating the development of communication ability of the affected individual.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of hearing loss in the newborn include mitochondrial abnormalities, genetic or congenital malformations, neurologic disorders or damage secondary to congenital infections such as cytomegalovirus (CMV), toxoplasmosis, rubella[2630]. Others are intrauterine exposure to ototoxic medications [2630] and HIV infection [19, 3133]. …”
Section: Introductionmentioning
confidence: 99%
“…Two PHIV children in the current study had present otorrhea whereas no HIV-uninfected child presented with otorrhea. Statistics were not completed given the small numbers, though other researchers have shown that HIV-infected children in Africa have significantly more present or past episodes of otorrhea [7] and significantly more episodes of recurrent otorrhea [12].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) reports the prevalence of chronic suppurative otitis media (CSOM) ranging from <1% to 7.8% [1]. Human immunodeficiency virus-infected (HIVinfected) children who are immunocompromised are at higher risk for this opportunistic infection [2][3][4][5][6][7][8]. Further, greater immunosuppression in HIV-infected children is associated with both a higher rate of otitis media and greater severity of otitis media [6] and more symptomatic HIV-infected children are at higher risk for recurrent episodes of otitis media [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…In Haiti, 37% pediatric patients with Tungiasis wounds reported pain. Chronic ear pain was prevalent in 44% of patients with HIV infection in Angola [43]. Twenty percent of pediatric patients with cerebral malaria in Mali reported headaches [44].…”
Section: Reviewmentioning
confidence: 99%